Write the following in the expanded form:
(i) (a + 2b + c)²
(ii) (2a - 3b - c)²
(iii) (-3x + y + z)2
(iv) (m + 2n – 5p)²
(v) (2 + x – 2y)²
(vi) (a² + b² + c²)²
(vii) (ab + bc + ca)²
(viii) (X/Y+Y/Z+Z/X)²
(ix) (a/bc+b/ca+c/ab)²
(x) (x + 2y + 4z)²
(xi) (2x - y + z)²
(xii) (-2x + 3y + 2z)²
Answers
Answered by
5
Given : (a + 2b + c)²
To find : expanded form:
Solution:
(a + 2b + c)²
= ( (a + c) + 2b)²
use identity
(x + y)² = x² + y² + 2xy
x = a + c
y = 2b
= (a + c)² + (2b)² + 2(a + c)(2b)
= a² + c² + 2ac + 4b² + 4ab + 4bc
= a² + 4b² + c² + 4ab + 4bc + 2ac
(a + 2b + c)² = a² + 4b² + c² + 4ab + 4bc + 2ac
Expand others similarly
Please post Question one by one
learn More:
Write 5 examples of the form (a + b + c)² and expand them using the ...
https://brainly.in/question/11762738
Use binomial theorem to expand (2+X)5 in ascending powers of x ...
https://brainly.in/question/11212431
Answered by
0
Answer:
from where did you get these questions btw❤
Similar questions